Ensiling Caged Layer Droppings with Grass and Rice Straw: Nutritional and Preservation Effects (Journal of the Bangladesh Agricultural University, 2025)
The research was conducted to evaluate the potential of ensiling caged layer droppings (CLD) with roadside green grass (RGG) and rice straw (RS) (Oryza sativa L.) in different amounts to assess the nutritional value of ensilage as well as preservation quality. Four different treatments T0 (0% CLD+ 45% RGG + 50% RS +5% molasses), T1 (10% CLD+ 35% RGG + 50% RS +5% molasses), T2 (20% CLD+ 25% RGG + 50% RS +5% molasses) and T3 (30% CLD+ 15% RGG + 50% RS +5% molasses) were prepared to evaluate the organoleptic quality (color, smell, texture, fungal growth), pH, nutritional composition (dry matter, crude protein, crude fiber,  ether-extract, ash), in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) at 0th, 7th, 14th, 21st, 28th days of ensiling. All parameters of different treatments changed significantly (p